Hermeneutika Hadis Sa’dudin Al-Utsmani: Studi Kitab Almanhaj Al-Wasthi Fi At-Ta’amil Sunnah An-Nabawiyyah (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
The hermeneutical approach in contemporary tafsir thought is often used as a reference when understanding the text of the Qur'an and Hadith. Hermeneutics serves as a tool for producing understanding and the most well-known methodology for understanding texts contextually and structurally well. The focus of this research will be to map understanding significantly through the hermeneutic theory of the hadiths of contemporary scholars, namely Sa'dudin al-Ustmani in his book "Manhaj Sunnah An-Nabawiyyah". This paper aims to explore methodological understanding through the theory of hermeneutic hadith which produces three important aspects in understanding the Sunnah An-Nabawiyyah, namely: First, Tasharruf in religious matters conveyed by the apostle. Second, the Tasharruf in the religion that is ijtihadi by the Prophet is the error of revelation and sometimes it is wrong but it does not continue in the error, usually there is revelation that justifies it. The revelation that justifies this is sometimes in the form of al-Qur'an, sometimes it is not al-Qur'an. Third, Tasharrufat in world affairs. The basic assumption of the author is to describe and describe the contemporary scholar Sa'dudin Al-Ustmani in his book "Manhaj sunah an-nabawiyah", which aims to provide an intermediate understanding in understanding the sunnah an-nabawiyah.
Keywords: Hermeneutics; Sa'dudin Al-Ustmani; Kitab; Sunnah; Annabawiyyah